Seroprevalence of hantavirus antibodies in Germany as determined by a new recombinant enzyme immunoassay - Zöller, Lothar; Faulde, M.; Meisel, H.; Ruh, B.; Kimmig, P.; Schelling, U.; Zeier, Martin; Kulzer, P.; Becker, C.; Roggendorf, M.; Bautz, Ekkehard K. F.; Krüger, D. H.; et al. (European journal of clinical microbiology & infectious diseases, 1995)
In order to elucidate the epidemiological importance of hemorrhagic fever with renal syndrome in Germany, the prevalence of antibodies against hantaviruses was determined in 13,358 sera from residents of various geographic regions, 1,284 sera from occupational risk groups and 287 sera from chronic hemodialysis patients. Serological investigations were performed using a highly specific transferable solid phase enzyme immunoassay based on the recombinant nucleocapsid proteins of a Hantaan and a Puumala serotype strain. The overall antibody prevalence was found to be 1.68 %. In the serum panels from western and southern Germany, it was determined to be 1.83 % on average in contrast to only 0.8 % in the panel from eastern Germany. An endemic focus revealing an antibody prevalence of 3.12 % was detected in a low-mountain area called Suebian Alb, which is located in the federal state of Baden-Württemberg. Occupational risk groups and a group of chronic hemodialysis patients showed a significantly elevated antibody prevalence ranging from 3.3 % to 10 %. The Puumala serotype was found to be the prevailing virus, but the percentage of sera predominantly recognizing the Hantaan nucleocapsid protein increased towards the south and the east and was significantly elevated in dialysis patients.
Gesehen am 05.09.2024